PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. JASA MANAJEMEN KONSTRUKSI PALEMBANG - S Salman; Rati Mayasari (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
Motivation and Leadership in combination then theoretically will affect the performance. For Motivation and Leadership will be very effective to improve the performance of subordinates, if he could give a boost to democracy and Persuasive manner. Because it is suspected there are positive influence between motivation and leadership together the Employee Performance.Without ruling out other factors, the authors saw that the factors Motivation and Leadership is a factor that needs serious attention in connection with efforts to improve employee performance. This is based on the fact that the factor of motivation and leadership is an aspect of humanity that is the mental attitude (behavior) people to use their skills and expertise to do the job for the achievement of high performance. Keywords: Leadership, Motivation and Employee Performance